2014
DOI: 10.3938/jkps.64.910
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor blending ratio dependence of bulk heterojunction organic photovoltaic devices

Abstract: Bulk heterojunction (BHJ) organic photovoltaic (OPV) devices are generally composed of a blend film of a -conjugated polymeric electron donor and a C60 derivative electron acceptor intercalated between an anode and a cathode, typical of a two-dimensional device structure. Often, a regioregular poly(3-hexylthiophene) (rr-P3HT) and indene-C60 bisadduct (ICBA) blend film is used as the BHJ active layer instead of the conventional P3HT and phenyl-C61-butyric acid methyl ester (PCBM) blend film due to the ICBA devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Interestingly, the degrees of the red shifts were virtually unaffected by the side-chain lengths of all the pristine films. In addition, well-resolved fine peaks were found in the UV–Vis spectra of all pristine films, which is known to be a sign of the pronounced interchain interaction-induced aggregation ability of the rr-polythiophenes, which has been reported in detail elsewhere [ 44 , 56 ]. If one takes the energetically lowest shoulder peak centered at ~602 nm, the red-shift is up to ~0.67 eV.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, the degrees of the red shifts were virtually unaffected by the side-chain lengths of all the pristine films. In addition, well-resolved fine peaks were found in the UV–Vis spectra of all pristine films, which is known to be a sign of the pronounced interchain interaction-induced aggregation ability of the rr-polythiophenes, which has been reported in detail elsewhere [ 44 , 56 ]. If one takes the energetically lowest shoulder peak centered at ~602 nm, the red-shift is up to ~0.67 eV.…”
Section: Resultsmentioning
confidence: 55%
“…Notably, a blending ratio of 1:0.7 was chosen for comparison with the optimized device parameters obtained using commercial P3HT. Our previous study focused on the blending ratio-dependent device performance and showed that the optimum blending ratio to obtain a statistically reliable and relatively high PCE of >4% was approximately 1:0.7 [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Summing up, unlike PE(I), the PE(P) is not effectively affected by the blending process. It is noteworthy that the conventional fullerene blend systems, e.g., PTB7:PC71BM [32] and P3HT:PC61BM, [7] have shown a systematic reduction in the lifetimes of PE originated from polymeric donors upon blending with fullerene acceptors. This difference can be recognized more clearly by exploring the kinetic decay traces extracted from the threedimensional TAS spectra of various samples, as shown in Figures 2 and 4.…”
Section: Exciton Dynamics Of P:i Blend Systemsmentioning
confidence: 99%
“…Nevertheless, this spectral extension is achieved by using noble NFA materials coupled with suitable polymers as a bulk heterojunction (BHJ) active layer. The benefits of NFA systems are clearly recognized by comparing with solar cells that comprise fullerene derivatives and, for instance, narrow bandgap polymers [6] or polythiophene derivatives [7].…”
Section: Introductionmentioning
confidence: 99%
“…se analisar os espectros de absorção dos sistemas apresentados na Figura 24 notam-se amplo espectro de absorção no intervalo de 300-650 nm. Onde a região característica de moléculas de PC 61 BM se encontra na faixa de comprimento de onda de 300-350 nm(YI et al, 2014) e a região característica do P3HT é observada no intervalo de comprimento de onda entre 400 nm e 650 nm (BRABEC;DURRANT, 2008). Além disso, observa-se uma nítida mudança no comportamento estrutural dos filmes da mistura P3HT:PC 61 BM com a temperatura dos substratos.…”
unclassified